2013
DOI: 10.1002/chem.201302378
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Synthesis and Characterization of New Actinide Borates, AnB4O8 (An=Th, U)

Abstract: New actinide borates ThB4O8 and UB4O8 were synthesized under high‐pressure, high‐temperature conditions (5.5 GPa/1100 °C for thorium borate, 10.5 GPa/1100 °C for the isotypic uranium borate) in a Walker‐type multianvil apparatus from their corresponding actinide oxide and boron oxide. The crystal structure was determined on basis of single‐crystal X‐ray diffraction data that were collected at room temperature. Both compounds crystallized in the monoclinic space group C2/c (Z=4). Lattice parameters for ThB4O8: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…More recently, however, the remediation and sequestration of legacy waste has become more pressing and is one reason for the current more comprehensive research efforts . As part of our program to prepare different classes of materials for potential use in future nuclear waste forms, we have focused on uranium borates as one class of materials that can lead to structure types practical for nuclear waste forms because uranium borates have been investigated in the past and numerous structures have been observed. As part of this effort, there exists the need to understand uranium cation stability and mobility in the environment and uranium complexation, crystal, and redox chemistry. In aqueous conditions, uranium­(VI) and -(IV) are the most stable among the four accessible oxidation states of uranium and, thus, the most prevalent in both synthetically derived compounds and reported minerals; comparatively, uranium­(V) and -(III) are considerably less stable .…”
mentioning
confidence: 99%
“…More recently, however, the remediation and sequestration of legacy waste has become more pressing and is one reason for the current more comprehensive research efforts . As part of our program to prepare different classes of materials for potential use in future nuclear waste forms, we have focused on uranium borates as one class of materials that can lead to structure types practical for nuclear waste forms because uranium borates have been investigated in the past and numerous structures have been observed. As part of this effort, there exists the need to understand uranium cation stability and mobility in the environment and uranium complexation, crystal, and redox chemistry. In aqueous conditions, uranium­(VI) and -(IV) are the most stable among the four accessible oxidation states of uranium and, thus, the most prevalent in both synthetically derived compounds and reported minerals; comparatively, uranium­(V) and -(III) are considerably less stable .…”
mentioning
confidence: 99%
“…In 1986, K 6 {UO 2 [B 16 O 24 ­(OH) 8 ]}­(H 2 O) 12 , the first actinide borate, was obtained through a slow evaporation method . Subsequently, a number of uranyl borates have been reported, e.g., by Gasperin, Wang, Wu and Hao, etc. The compounds reported by Gasperin were prepared through high-temperature, solid-state reactions, and these conditions primarily led to BO 3 triangles as expected. In contrast, Wang et al reported the use of what is termed a hydroflux of H 3 BO 3 with low water content under mild heat near 200 °C for the synthesis.…”
Section: Introductionmentioning
confidence: 89%
“…Whereas, in the structure of αmodification boron atoms occupy corner sharing BO 4 -tetrahedra and BO 3 -triangles forming 1D zigzag chain [30]. ThB 4 O 8 structure exhibits infinite chains, which consist of [B 2 O 4 ] 5− tetrahedral borate groups that are connected through one common oxygen atom [31]. Monocationic borates of pentavalent elements have only isolated BO 4 tetrahedra [32].…”
Section: Combined Structural Unitsmentioning
confidence: 99%